OPTIMALISASI HMI SCADA UNTUK MONITORING DAN KONTROL REPEATER RADIO KOMUNIKASI MENGGUNAKAN MODEM GPRS INTEK J65i-X - Aufa, Al Anamila Nur; Yuwono, Teguh (Gema Teknologi, 2014)
Al Anamila Nur Aufa, Teguh Yuwono, in paper SCADA HMI optimization for monitoring and control repeater using radio communication modem GPRS INTEK J65i–X explain that radio communications at PT PLN ( Persero ) APD Central Java and Yogyakarta is still a major communication medium for coordinating the work , both maintenance and handling of interference between units . Repeaters in this case an important role in the communication process between APD dispatcher JTY with Area - Area and officers in the field because of the presence of the communication range of the repeater spacing becomes wider . In operation repeaters can be susceptible to interference that can result in radio communications in the areas covered by the repeater to be disrupted so that the communication between the dispatcher APD JTY with Area - Area and field workers to be blocked. Handling repeater for this disorder is not maximized due to the lack of real time monitoring of the state of the repeater , so that when the repeater impaired in the device or on the supply , the clerk did not know in person and just waiting for a report from the repeater keeper at any time at the shelter is not a repeater . There needs to be a device that can monitor the state of the repeater , which if detected interference at the source , supply and radio , PPE JTY officer may direct monitoring , so that it can assist in the handling and analysis of causes of hearing disorders without having to come to the site . GPRS Modem Utilization Intek J65i - X allows retrieval status of the repeater equipment where it can not be done at this time . With facilities tapped digital inputs and digital outputs on the modem , any condition of equipments such as radio signal repeater RX , TX radio signal , battery , charger and 220V supply state of the supply voltage can be detected . From changes in the supply voltage available , can be detected by a GPRS modem Intek J65i - X so that when there is an interruption in the HMI SCADA can termonitoring in real time . With the monitoring and control of a radio repeater communications , personnel no longer need to go to the location (site ) only to find the cause of the disturbance . Interference analysis can also be performed before treatment is held further disruption . Reset control radio can also be done quickly if the radio have to hang in its operation , so that the future will be able to improve the performance of SCADA systems PT PLN ( Persero ) APD Central Java and DI Yogyakarta. Keywords : repeater , modem GPRS Intek J65i - X , auxiliary relays , monitoring and control , HMI SCADA